Detection of Bartonella sp. and a novel spotted fever group Rickettsia sp. in Neotropical fleas of wild rodents (Cricetidae) from Southern Brazil. (December 2020) - Schott, Diogo; Umeno, Karen; Dall'Agnol, Bruno; Souza, Ugo Araújo; Webster, Anelise; Michel, Thais; Peters, Felipe; Christoff, Alexandre Uarth; André, Marcos Rogério; Ott, Ricardo; Jardim, Márcia; Reck, José
Highlights: Here, we investigated the pathogens in fleas 61 from 350 Neotropical rodents. Five genotypes of Bartonella sp. were identified in two species of fleas. A novel Spotted Fever Group Rickettsia was found in rodent fleas. This is the first description of a Spotted Fever Rickettsia in Neotropical fleas. Abstract: The Neotropical region shows a great diversity of fleas, comprising more than 50 genera. The importance of the study of fleas is linked to their potential role as disease vectors. The aim of this study is to investigate the presence of Rickettsia spp. and Bartonella spp. in Neotropical fleas collected from wild rodents in Southern Brazil. From 350 rodents captured, 30 were parasitized by fleas. A total of 61 fleas belonging to two genera and six different species were collected ( Craneopsylla minerva minerva, Polygenis occidentalis occidentalis, Polygenis platensis, Polygenis pradoi, Polygenis rimatus, and Polygenis roberti roberti ). In 13 % of fleas of three different species ( C. minerva, P. platensis, and P. pradoi ) Rickettsia sp. DNA was found. Phylogenetic analysis of concatenated sequences of gltA, htrA, and ompA genes showed that Rickettsia sp. found in rodent fleas (referred as strain Taim) grouped together with Spotted Fever Group Rickettsia . In reference to Bartonella spp., five genotypes were identified in seven fleas of two species ( C. minerva and P. platensis ) and in five rodent spleens. Also, 207 frozen samples of wild rodents were screened for these pathogens: while none was positive for Rickettsia spp.; five rodent spleens were PCR-positive for Bartonella spp.. Herein, we show the detection of potential novel variants of Bartonella sp. and Rickettsia sp. in fleas collected of wild rodents from Southern Brazil. Further studies are needed to fully characterize these microorganisms, as well as to improve the knowledge on the potential role of Neotropical flea species as diseases vectors.